A functional equation characterizing cubic polynomials and its stability - Soon-Mo Jung; Prasanna K. Sahoo (International Journal of Mathematics and Mathematical Sciences)
We study the generalized Hyers-Ulam stability of the functional equation f[x1,x2,x3]=h(x1+x2+x3).